Long non-coding RNAs as novel therapeutic targets in cancer. (August 2016) - Lavorgna, Giovanni; Vago, Riccardo; Sarmini, Mohamad; Montorsi, Francesco; Salonia, Andrea; Bellone, Matteo
Graphical abstract: Abstract: Thanks to impressive technology advancements, pervasive expression of non-coding RNAs (ncRNAs) has been recently identified in the genome of numerous cancers. Long ncRNAs (lncRNAs) belong to a new class of ncRNAs including tens of thousands different species. A fraction of these molecules shows a striking cancer-enriched expression pattern, suggesting an essential role in tumor cells and, possibly, a utility in therapeutic terms. This review aims at summarizing current knowledge for the identification and validation of lncRNAs as therapeutics targets in tumors. Both in-silico and wet-biology resources are presented in relation to the many challenges that the scientific community still needs to address in terms of lncRNA identification, stratification, patient personalization, drug delivery and toxicity.